Exosomal BMPR2 Macromolecule Facilitates Alveolar Epithelial Cell Repair Through Functional Complex Formation with BMPR1B in Acute Lung Injury - Yun X; Chen Z; Li F; Shen F; Zhang L; Yuan J (International Journal of Nanomedicine, 2025)
Xiang Yun,1– 3 Zhen Chen,4 Fei Li,1 Fuhai Shen,1 Lin Zhang,2,3,5 Juxiang Yuan1 1School of Public Health, North China University of Science and Technology, Tangshan, 063000, People’s Republic of China; 2Clinical Medical Research Center for Women and Children Diseases, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250001, People’s Republic of China; 3Key Laboratory of Occupational Exposure and Fertility Preservation for Women of Shandong Health Commission, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250001, People’s Republic of China; 4School of Public Health, Shandong Second Medical University, Weifang, 261053, People’s Republic of China; 5Henan Medical Key Laboratory for Research of Trauma and Orthopedics, The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, 453000, People’s Republic of ChinaCorrespondence: Juxiang Yuan, School of Public Health, North China University of Science and Technology, Tangshan, 063000, People’s Republic of China, Email yuanjx@ncst.edu.cn Lin Zhang, Clinical Medical Research Center for Women and Children Diseases, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250001, People’s Republic of China, Tel +86-531-68795920, Email zhanglin8901@sdu.edu.cnBackground: Acute lung injury (ALI) poses significant clinical challenges due to its irreversible alveolar damage and the limitation of available regenerative therapies. Emerging evidence suggests that macrophage-epithelial crosstalk plays a pivotal role in lung repair; however, the specific molecular mediators underlying this process remain largely undefined.Methods: To address this gap, we isolated and characterized macrophage-derived exosomes (MD-Exos) using dynamic light scattering, transmission electron microscopy (TEM), and immunoblotting. Proteomic analysis and molecular docking were employed to reveal interactions between BMPR2 on exosomes and BMPR1B on epithelial cells. Single-cell RNA sequencing (scRNA-seq) was utilized to map alveolar cell dynamics. Biochemical assays and confocal colocalization were performed to validate SMAD1 signaling activation. The biodistribution of exosomes was tracked via near-infrared imaging, and AT2-to-AT1 transdifferentiation was assessed through multiplex immunofluorescence and pseudotime trajectory analysis.Results: Proteomic profiling of MD-Exos identified BMPR2 as the predominant component. Molecular docking studies confirmed a strong binding affinity between exosomal BMPR2 and epithelial BMPR1B. Single-cell RNA sequencing and biochemical analyses revealed significant alterations in alveolar macrophage (34% vs 27%) and epithelial cell populations during injury, accompanied by enhanced cellular communication. The characterized macrophage-derived exosomes (163.6 ± 70.2 nm) demonstrated efficient pulmonary targeting, with peak accumulation occurring at 4 hours post-administration. Mechanistically, the formation of the BMPR2-BMPR1B complex activated SMAD1-dependent signaling pathways, as evidenced by strong BMPR1B-SMAD1 colocalization (correlation coefficient 0.94 ± 0.02) and enhanced ID1 expression.Conclusion: The BMPR2-BMPR1B interaction was demonstrated to accelerate type II to type I alveolar epithelial cell transdifferentiation, thereby facilitating tissue repair in ALI. Comprehensive toxicological assessment confirmed the safety profile of exosome administration across major organ systems. These findings establish exosomal BMPR2 as a crucial mediator of pulmonary repair through specific molecular recognition and signaling activation, providing new therapeutic strategies for treating acute lung injury. Keywords: exosomal BMPR2, BMPR1B, alveolar epithelial cells, cellular repair, protein-protein interaction